The initiative to investigate the management of Pericarditis in Africa (IMPI) Registry : a substudy on the causes of constrictive pericarditis and predictors of mortality in patients with constrictive pericarditis requiring pericardiectomy at Groote Schuur Hospital (The Constrictive Pericarditis Substudy) - Mutyaba, Arthur Kaggwe (Department of Medicine, 2016)
Background: Causes of constrictive pericarditis and predictors of peri-operative outcome following pericardiectomy are not clearly elucidated, especially in Africa, where disease characteristics differ from developed countries. Furthermore, the impact of HIV/AIDS on pericardial constriction and outcomes following surgery is unknown. We set out to investigate the causes of constrictive pericarditis, the outcomes after pericardiectomy and the predictors of mortality in Cape Town, South Africa during a 22-year period of high HIV/AIDS prevalence. Methods: A retrospective review of records of all patients who underwent pericardiectomy for constrictive pericarditis at Groote Schuur Hospital from 1 January 1990 to 31 December 2012 was performed.